Impact of Economic Planning on Sustainable Development in Nigeria - Brown, Ewubare, Dennis (Asian Development Policy Review, 2019)
This paper examined the impact of economic planning on sustainable development in Nigeria. The specific objectives were to: examine the impact of planned investments on economic, community and social services on poverty reduction and income inequality. The Fully Modified Least Squares and Granger causality tests were applied in analyzing the data sourced from the Central Bank of Nigeria Statistical Bulletin, National Bureau of Statistics and the World Bank. The cointegrating regression results show that planned investments in economic services exert significant positive impact on poverty rate and Gini index. On the contrary, planned investment on community and social services has significant negative impact on poverty rate and Gini index. 1 percent increase in investments in community and social services reduces poverty rate by 0.815 percent and 0.429 percent of income inequality. It therefore follows from the result that investments in community and social services play a key role in achieving sustainable development goals by mitigating the incidences of poverty and inequality. The Granger causality test results show that unidirectional causality runs from planned investment on economic services to both poverty rate and income inequality. Similarly, unidirectional causality flows from planned investment on community and social services to income inequality. The results further revealed that joint causality flows from the explanatory variables to poverty rate and inequality. This finding indicates that the underlying measures of economic planning are jointly important in predicting changes in sustainable development in Nigeria. Accordingly, the study recommends that policy makers should prioritize investment in education, health and other aspects of community and social services in to engender sustainable development.